Painting Writing, Writing Painting: Thinking, Seeing, and Problem Solving Through Story. (17th December 2017) - Martens, Prisca; Martens, Ray; Doyle, Michelle Hassay; Loomis, Jenna; Fuhrman, Laura; Stout, Robbie; Soper, Elizabeth
Abstract: The purpose of this article is to share how the authors supported kindergartners' and first graders' developing creativity through stories they composed in writing and art. Over eight years, the authors explored ways to use picturebooks as mentor texts to help students explore how the authors and artists create meaning multimodally. This article shares minilessons and examples of how students creatively and imaginatively told their stories; learned to think, see, and reason; and invented and problem solved their stories, seamlessly weaving their meanings into writing and art.